Amwal Zakat Management: A Case Study in Yogyakarta - Mohammad Jailani; Waharjani Waharjani (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
Zakāh collection in Nitikan village of Yogyakarta has experienced an increase since 2017, which previously had been stagnant. This paper aims to investigate the current development of the zakāh collection in that area, as it represents Muhammadiyah's efforts in the religious philanthropic movement. This is a qualitative study, with the data obtained from participatory observation and in-depth interviews with zakāh stakeholders. This study finds that the improvement of the zakāh collection has contributed to several factors. These include the role of ulama and Bapelurzam of Muhammadiyah, leading to the increasing trust of the people. This is strengthened by the changing paradigm of the muzakki regarding zakāh al-māl from merely gold and silver into any properties equal to niṣāb and has reached the haul; and the strong determination of mustaḥiq to transform themselves into muzakki.